The role of orlistat in management of obesity - Samuel Oetoro (World Nutrition Journal, 2022)
Rapidly rising prevalence of obesity is alarming. Obesity predisposes to co-morbidities like hypertension, type 2 diabetes mellitus, dyslipidemias, thus substantially rising healthcare expenditure.